2012
DOI: 10.1002/gps.3791
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationships between depressive symptoms and white matter hyperintensities in older men and women

Abstract: Objective Associations between vascular disease and depression in late life, including increased white matter hyperintensities (WMHs), have been reported. Whether depression is an etiology or a consequence of vascular disease is still unknown. We investigated the temporal relationship between depressive symptoms and WMHs in older men and women. Methods We utilized data from 90 dementia-free older adults (39 women, 51 men), 57 years of age and older at baseline, from the neuroimaging substudy of the Baltimore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 111 publications
2
21
2
Order By: Relevance
“…The relationship between WMHs and the vascular depression hypothesis is further strengthened by studies demonstrating that WMHs are associated with treatment outcomes (Aizenstein et al, 2011;Firbank et al, 2007;Heiden et al, 2005;Taylor et al, 2014). However, as several other studies have failed to find the association between WMHs and depression, the vascular depression hypothesis is not universally accepted (Aizenstein et al, 2011;Dotson et al, 2013). The failure to find robust cross-sectional associations between cerebrovascular disease and LLD does not prove that WMH changes do not promote depression, but may suggest that the association with depression is weak given the large variability of WMHs across elderly individuals.…”
Section: Introductionmentioning
confidence: 90%
“…The relationship between WMHs and the vascular depression hypothesis is further strengthened by studies demonstrating that WMHs are associated with treatment outcomes (Aizenstein et al, 2011;Firbank et al, 2007;Heiden et al, 2005;Taylor et al, 2014). However, as several other studies have failed to find the association between WMHs and depression, the vascular depression hypothesis is not universally accepted (Aizenstein et al, 2011;Dotson et al, 2013). The failure to find robust cross-sectional associations between cerebrovascular disease and LLD does not prove that WMH changes do not promote depression, but may suggest that the association with depression is weak given the large variability of WMHs across elderly individuals.…”
Section: Introductionmentioning
confidence: 90%
“…However, other recent studies have suggested that this sequence could be bidirectional. 2 As I argue elsewhere, 3 the relationship between physical disease and mood disorder in the elderly is likely to be aetiologically complex and characterised by reciprocity.…”
Section: Edited By Kiriakos Xenitidis and Colin Campbellmentioning
confidence: 99%
“…The recent paper by Gunnell et al 1 and the accompanying editorial by Pitman & Caine 2 clearly outline the practice and principles of a contemporary approach to suicide prevention in mental health settings. However, I do not think the policy initiative that every patient with a serious mental illness or a recent episode of self-harm should be followed up within a week of discharge is really a high-risk approach to suicide prevention.…”
mentioning
confidence: 99%
See 2 more Smart Citations